An evaluative survey on satisfaction level of the selected female consumer's usage on counterfeit tops - Samante, Karen Joie A. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT Counterfeiting greatly violates intellectual property rights, and affects the economy, the industries, and the consumers (OECD, 2007). Aside from the decline of the economy due to the recession, counterfeiting is also one of the problems faced by the garment industry. This research is an evaluative survey on the satisfaction level of the selected female consumer‟s usage on counterfeit tops, specifically t-shirts and blouses. The researcher conducted focus group discussion (FGD) as a tool to create the survey questionnaire. It was also determined that tops are one of the common counterfeit apparel products purchased by the focus group respondents; hence the researcher selected tops to be the focus of the study. Purposive and snowball sampling were used in the selection of the fifty working female who are self- confessed users of counterfeit tops. The researcher determined the level of satisfaction of the respondents on the counterfeit t-shirts and blouses they purchased by subtracting their grade on expectations from their grades on actual experience. The differences of their expectation and actual experience were given a corresponding satisfaction level. The researcher found out that price and durability are the only factors which received a passing satisfaction level because Counterfeit tops that respondents purchased are cheaper yet can still be used after a number of times. iii However, style and design and construction received a failing satisfaction level because counterfeit tops cannot exactly copy the style, design, and quality of construction of original brands. Most of the counterfeit tops are defective that is why consumers were not able to achieve their expectations in terms of style and design and construction, It was also found out that the more regular buyers the respondents are, the lower they expect from the counterfeit tops which leads to the higher satisfaction level. The respondents‟ repeated experiences on purchasing and using counterfeit tops established lower standards of expectation on their next purchase; it is because they already accepted the characteristics and qualities of the items. This study recommends that fashion retailers compete through producing items that features the weakness of counterfeit items such as style and design and construction, and its strengths such as price and durability on market research. Furthers studies on (1) how economic status affects their willingness to spend and consume counterfeit tops, (2) locations where consumers purchased their counterfeit t-shirts and blouses, and (3) other types of counterfeit apparel products and their classes. Information on consumers‟ personality, attitudes, and needs in purchasing counterfeit t-shirts and blouses and the consumer‟s using and care practices on the items can also be added on the study.